Honey and Mumford learning style: creative thinking process in solving statistical problems - Rosita Dwi Ferdiani; Wahyudi Harianto (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research revealed the nature of students’ creative thinking processes with theoretical and pragmatic learning styles in solving problems. The creative thinking process of these students goes through the stages of synthesizing ideas, building ideas, planning the implementation of ideas, and implementing ideas. This research was conducted at one of the junior high schools in Pasuruan Regency, Indonesia. Prospective research subjects are second grade students, totaling 150 students. The research instrument is the researcher as the main instrument and is assisted by additional instruments, namely the learning styles questionnaire (LSQ), the creative thinking test presented in E-module using science, technology, engineering and mathematics (STEM) project-based learning, and interview guidelines. Based on the results of research on creative thinking processes in solving problems in students with theoretical learning styles and students with pragmatic learning styles, it can be concluded that there are differences in the creative thinking process at each stage, namely the stages of synthesizing ideas, building ideas, planning implementation of ideas, and implementing ideas. This difference is caused by differences in character between students with theoretical learning styles and pragmatic learning styles that influence students in building ideas to implement ideas.